EFEKTIVITAS PELAYANAN DALAM PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) DI KANTOR PERTANAHAN KOTA PEKANBARU PADA MASA PANDEMI COVID 19 - Junedi Parsaroan Siahaan; Harapan Tua RFS (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The need for land is increasing considering that Pekanbaru City is the capital of Riau Province and also the largest city in Riau Province. In this case, the government is trying to provide legal certainty to land owners through a complete systematic land registration program. This type of research uses a qualitative approach. The results of the study show that the covid 19 pandemic affects the effectiveness of services in a complete systematic land registration program. Factors that affect the effectiveness of services in a complete systematic land registration program at the Pekanbaru City Land Office during the covid 19 pandemic, namely the existence of butget cuts and the implementatiton of social distancing and WFH in the city of Pekanbaru. The need for land is increasing considering that Pekanbaru City is the capital of Riau Province and also the largest city in Riau Province. In this case, the government is trying to provide legal certainty to land owners through a complete systematic land registration program. The purpose of this study was to determine the effectiveness of services in a complete systematic land registration program at the Pekanbaru City Land Office during the covid 19 pandemic and to look at the factors that influence the effectiveness of services in a complete systematic land registration program at the Pekanbaru City Land Office during the covid 19 pandemic. This type of research uses a qualitative approach. The results of the study show that the covid 19 pandemic affects the effectiveness of services in a complete systematic land registration program. Factors that affect the effectiveness of services in a complete systematic land registration program at the Pekanbaru City Land Office during the covid 19 pandemic, namely the existence of butget cuts and the implementatiton of social distancing and WFH in the city of Pekanbaru. . Keywords: Service Effectiveness, Complete Systematic Land Registration Program, Covid 19 Pandemic, Pekanbaru City Land Office